Minors and social assistance in the Legislature during the governorship of José Luis Cantilo. Province of Buenos Aires, 1922-1926 (Quinto Sol, 2025)
This article analyzes bills presented to the Legislature of the Province of Buenos Aires, Argentina, during the governorship of José Luis Cantilo, both by the Executive Branch and by some legislators. It seeks to observe, through their foundations and central proposals, how social policy for children was understood, paying special attention to the perception of the needs to be addressed, the role of the State, and the role of private assistance in operation.The analysis presented focuses on proposals that, although most did not translate into laws after their presentation, allow us to see the slow redefinition of the spaces for state intervention regarding minors in the first decades of the 20th century. The legislative bills and parliamentary discussions recovered contribute to illuminating the reformist landscape of the period studied, beyond the concrete results.
Keywords: State; social policy; childhood; institutions